Biochemical and Hematological Alterations in Fish Infected with Bothriocephalus acheilognathi - Dhannoon, Nour Abdulehsan; Hashim, Dalia Sudad; Hassan, Shahla Fathola (American Journal of Biology and Natural Sciences, 2025)
In the current study, the influence of natural infection of Bothriocephalus acheilognathi on some biochemical constituents and haematological parameters of the fish suspension and the muscle content of three fish species; Cyprinus carpio, Silurus triostegus and Liza abu, were determined. A total of 108 fish were considered, with 66 infected and 42 uninfected. Infected fish also showed significantly lower protein and fat muscle content, but no significant differences in moisture value were observed when compared to uninfected fish. Serum total protein, cholesterol, and glucose levels of infected fish were shown to be decreased. Hematological analysis revealed reduced RBC and PCV values, while WBC values increased significantly in the infected group. These results were indicative that B. acheilognathi infection results in deterioration of both the physiological and nutritional status of fish and perhaps suppressed growth performance in aquaculture.